A Brief Introduction to Antibody–Drug Conjugates for Toxicologic Pathologists. (October 2018) - Mecklenburg, Lars
Antibody–drug conjugates (ADCs) are an emerging class of anticancer therapeutics, delivering highly cytotoxic molecules directly to cancer cells. ADCs are composed of an antibody, a small molecule drug, and a linker attaching one to another. Antibodies are directed to a large variety of antigens overexpressed on tumor cells, tumor vasculature, or tumor-supporting stroma. After internalization, the ADC is transferred to lysosomes where the cytotoxic component is released, finally killing the target cell. All ADCs are administered via intravenous injection. Once in the circulation, linker stability in plasma is of high importance. In vivo studies in animals address the release of payload over time and typically measure total antibody, conjugated ADC, and free drug. ADC development is driven by ICH (International Council for Harmonisation) guidelines S6(R1) and S9. Dose-limiting toxicities of current ADCs are mainly associated with the payload and correlate well between clinical trials and nonclinical studies in rodents and nonrodents. This mini review is intended to provide general information about ADCs in oncology and shall assist the toxicologic pathologist in correctly interpreting morphological findings acquired in toxicity studies with this entity.